Sustainable air-conditioning for office building in the tropics - Rao, S.P.; Ressang, A.M. (2008)
Tropical climates are thermally uncomfortable and are mostly unhealthy to the occupants of the modern skyscrapers both residential and commercial buildings. The outdoor of air dry bulb temperatures are on the hot side coupled with high relative humidity's. The population living in the tropics, especially in countries like Malaysia, is affluent and can afford to air condition their residences and offices. Installation of air-conditioners is almost synonymous with prestige. This way of living leads to increased electricity usage and energy consumption in the buildings. However, switching- off the air-conditioning is not an option for the modern day buildings, as it would affect the health of the people as well as their productivity. This paper proposes innovative indoor units that will contribute to energy conservation by utilising principles of partial air-conditioning. The outdoor units can be utilised for clothes drying or for providing hot water to the occupants of the building of residential buildings thus, reducing the energy requirements in the buildings. Thus, the utilisation of partial air-conditioning will lead to enormous savings in energy consumption in the buildings.